Diversidade morfológica, agronômica e potencial para produção de etanol de germoplasma de batata-doce - Alves, Rodrigo Pereira (2014)
The sweet potato (Ipomoea batatas L.) is a dicotyledonous species of Convolvulaceae family, cultivated worldwide, with a low production cost and high economic return. Can be utilized in food and feed and ethanol production. The present study aimed, morphological, agronomic and biochemical characterization of sweet potato from the Active Germplasm Bank of UFS access. The experiment was conducted at the Experimental Farm " Rural Campus " UFS, located in the municipality of São Cristóvão - SE, using a randomized block design with 73 treatments (accessions of sweet potato), and two repetitions. In morpho-agronomic characterization it was found that descriptors sheet provided the variability among accessions. It was also observed that most accessions showed resistance to soil insects. The fresh and dry weight of shoots showed results ranging from 0,45 t ha-1 to 12,16 t ha-1 and 0,17 t ha-1 to 2,71 t ha-1, respectively. For total root yield variable, the values ranged from 1,20 to 10,89 t ha-1. The accessions showed excellent results for the dry root mass averaging 30,77 %. The starch content varied between 11,56 and 27,07 % , the yield of starch per hectare ranged from 0,30 to 2,39 t ha-1 and amylose content showed values between 11,57 to 32,72 %. While the ethanol yield in L ha-1 ranged from 198-1576 L h-1, the ethanol yield on L t-1 had an average of 142,67 L t-1. The results showed that the Active Germplasm Bank of UFS presents a wide phenotypic and genotypic variability, with different skills.